Morphological and Functional Characteristics of Animal Models of Myocardial Fibrosis Induced by Pressure Overload - Yuejia Ding; Yuan Wang; Qiujin Jia; Xiaoling Wang; Yanmin Lu; Ao Zhang; Shichao Lv; Junping Zhang (International Journal of Hypertension)
Myocardial fibrosis is characterized by excessive deposition of myocardial interstitial collagen, abnormal distribution, and excessive proliferation of fibroblasts. According to the researches in recent years, myocardial fibrosis, as the pathological basis of various cardiovascular diseases, has been proven to be a core determinant in ventricular remodeling. Pressure load is one of the causes of myocardial fibrosis. In experimental models of pressure-overload-induced myocardial fibrosis, significant increase in left ventricular parameters such as interventricular septal thickness and left ventricular posterior wall thickness and the decrease of ejection fraction are some of the manifestations of cardiac damage. These morphological and functional changes have a serious impact on the maintenance of physiological functions. Therefore, establishing a suitable myocardial fibrosis model is the basis of its pathogenesis research. This paper will discuss the methods of establishing myocardial fibrosis model and compare the advantages and disadvantages of the models in order to provide a strong basis for establishing a myocardial fibrosis model.